A importância do estágio supervisionado no curso de licenciatura em educação do campo: artes e música (Tocantinópolis/TO) - Santos, Rayane Bandeira (Universidade Federal do Tocantins, 2020)
The present work is theme "The importance of supervised internship of the Course of Degree in Field Education: Arts and Music (Tocantinópolis/TO) ", having as main objective to analyze the importance of supervised internship in the training of educators in the course field. The Supervised Curricular Internship presents itself as one of the most important elements to be performed in the entire area of professionalization, bringing something relevant in the academic and professional life of the student. This work is configured as a descriptive research, with a qualitative approach, being initially developed through bibliographic research in which data were collected from books, articles and through subjects related to the stage present in the pedagogical project of the course (PPC) together with contributions present in the respective answers collected from questionnaires with questions sent to the professors of the course participating in the research. In a second moment of the research, a data collection was also performed through my personal experience during my internships and the preparation and application of open questionnaires aimed at graduates and graduates of the Course of Degree in Field Education: Arts and Music (Tocantinópolis /TO). Thus, we sought to elucidate the importance of supervised internship, as well as questions related to its execution, from, especially, from the point of view of people who experienced it in the course